The Influence of Price Perceptions and Product Quality Perceptions on Toyota Rush Purchase Decisions in Auto 2000 Kenjeran Branch Surabaya - A’isy Sufyaan Alim Pamuji; Hery Pudjoprastyono (PT FORMOSA CENDEKIA GLOBAL, 2023)
Based on data from GAIKINDO (Indonesian Association of Automotive Industries) it shows a decline in sales at the Toyota Rush in 2020 and specifically at the Auto 2000 Kenjeran Branch in Surabaya. This indicates a decrease in purchasing decisions. The purpose of this study was to analyze and determine the effect of price perceptions and product quality perceptions on purchasing decisions for the Toyota Rush Car at Auto 2000 Kenjeran Surabaya Branch. This research method uses quantitative methods. The population in this study were Toyota Rush Car Buyers at the Auto 2000 Kenjeran Surabaya Branch. The sample in this study used purposive sampling and a population of 90 respondents and used the (Partial Least Square)PLS analysis tool. The results of this study are 1. Based on the results of calculations and data analysis it is known that Price Perception has a significant positive effect on Toyota Rush purchasing decisions, which means if Price Perception is in line with consumer purchasing decisions. 2. Based on the results of calculations and data analysis it is known that the Perceived Product Quality has a significant positive effect on the Toyota Rush purchasing decision, which means that if the Perceived Product Quality of the Toyota Rush increases, it will be in line with the consumer purchasing decision.